การวิเคราะห์ปัจจัยที่ส่งผลต่อการบริหารจัดการที่เป็นเลิศของโรงเรียนอนุบาลเอกชน - สุทธนา ฮั่นเกียรติพงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The research aimed to analyze the factors affecting excellent administration of private kindergartens in Thailand. The sample population were 81 private schools, offering courses at the pre-primary level, which passed the assessment by Office of National Education Standards for Quality Assurance (ONESQA) and received a Royal-Sponsored award from academic years 2004-2008. Data collection was divided into 2 phases : phase 1 distribution of questionnaires concerning the factors affection excellent administration of private kindergartens, phase 2 interviews with administrators of the private kindergartens and other persons concerned to collect qualitative data. The data derived from questionnaires concerning the factors affecting excellent administration of private kindergartens and the level of excellent administration of the private kindergartens were analyzed through the use of SPSS for Windows. A content analysis was used to analyze qualitative data. The research findings turned out as follows. 1. For excellent administration of private kindergartens, the administration for output was rated at the highest level, while the administration for personnel, school and community relations, teaching or educational provision process and general administration were rated at a high level. 2. For the factors affecting excellent administration of private kindergartens, there were 4 independent variables that could explain variances of excellent administration of the private kindergartens at the percentage of 79.82. 1) school factors, 2) teacher and other personnel factors, 3) administrator factors, and 4) external environment factors.